Peningkatan Keterampilan Produksi dan Pemasaran Produk Unggulan Madu di Desa Margacinta, Kabupaten Pangandaran, Jawa Barat - Widyaningrum, Bakti; Mutolib, Abdul; Helbawanti, Octaviana; Anita Eka, Putri; Erviyana, Windiastuti (Research and Social Study Institute (RESSI), 2024)
Margacinta Village has abundant tourism potential, one of which is natural honey bee cultivation. Honey farmers in Margacinta Village are organized into the Taruna Karya Honey Farmer Group. During the harvest season, the honey produced by farmers is abundant (60 to 80 liters, but during the rainy season, honey farmers in Margacinta Village have the potential to experience crop failure, this clearly threatens the economy of honey farmers in Margaacinta Village. The implementation of this service is to develop tourism with the concept of agro-eduwisata. Development is carried out in several stages, starting from education, training, and practice for honey farmers, establishing mini ecosystems as a source of bee feed and agro-educational destinations, and marketing on various platforms. The service was carried out in response to community problems in Margacinta Village, so that the purpose of this service was to improve the economy of the community in general, the Taruna Karya Farmer Group in particular. The targeted outputs are the formation of honey village agro-tourism, the publication of the Apiscerana honey bee cultivation module, the existence of standard packaging standards for raw products, marketing of local products and honey village agro-tourism packages, the formation of mini bee ecosystems, and honey extraction using machine extractors so that the honey obtained is of higher quality.